(untitled) - Du Bois, W. E. B. (New York, 2007)
This is the classic history of the African peoples in Africa and the New World, a repudiation of the absurd belief, widely held in the post-Civil War period, that Africans had no civilization but the one foisted upon them by their slave trading captors. Writing for a popular audience in 1915, DuBois, one of America's greatest writers, lays out in easy-to-read, nonacademic prose the striking and illustrious story of the complex history and varied cultures of Africa, from the art and industry of the peoples of the continent to the dramatic impact the slave trade had both in Africa and on her descendents in the Western Hemisphere. Boldly proud and beautifully written, this essential work will delight readers of American and African history as well as students of great American literature.
Keywords: Africa,Châu Phi; History.,Lịch sử